Comparing the low‐salinity tolerance of Ulva species distributed in different environments. Issue 1 (6th December 2012) - Ichihara, Kensuke; Miyaji, Kazuyuki; Shimada, Satoshi
Summary: The green macroalgal genus Ulva (Ulvales, Ulvophyceae, Chlorophyta) is distributed worldwide from marine to freshwater environments. Comparative analyses of hyposalinity tolerance among marine, brackish, and freshwater Ulva species were performed by fluorescein diacetate viability counts. The subtidal marine species Ulva sp., collected from a depth of 30 m, showed the poorest tolerance to low salinity. This species died in 5 practical salinity units (PSU) artificial seawater or freshwater within 1 day. Its closely related species U. linza L. (an intertidal species) and U. prolifera Müller (a brackish species) showed varying tolerances to low salinity. After 7 days of freshwater exposure, the viability of U. linza L. decreased to approximately 20%, while U. prolifera Müller showed nearly 100% viability. The freshwater species U. limnetica Ichihara et Shimada, not yet found in coastal areas, was highly viable in seawater.